US patent no. 7,571,062 B2: Digital flowmeter - Henry, M; Clarke, D; Vignos, J (United States Patent and Trademark Office, 2009)
A controller for a flowmeter includes an input module operable to receive a sensor signal from a sensor connected to a vibratable flowtube. The sensor signal is related to a fluid flow through the flowtube. The controller also includes a signal processing system operable to receive the sensor signal, determine sensor signal characteristics, and output drive signal characteristics for a drive signal applied to the flowtube. An output module is operable to output the drive signal to the flowtube and a control system is operable to modifY the drive signal and thereby maintain oscillation of the flowtube during a transition of the flowtube from a substantially empty state to a substantially full state.